Editorial from Editor-in-Chief - Chapagain, Pralhad (International Journal on Engineering Technology, 2025)
24th April 2025 Dear Colleagues, Contributors, and Readers, I am proud to announce the release of the special edition of the International Journal on Engineering Technology (InJET), featuring the KEC Conference 2025 Proceedings, Volume VII. As the Editor-in-Chief of the KEC Conference 2025, I extend my warmest greetings to all participants contributing to this academic endeavor. The theme of the conference, "Dedicated to Enhancing Research Ability," highlights the importance of research in shaping the future of engineering and technology. We remain committed to fostering collaboration and advancing knowledge. In its seventh edition, the KEC Conference continues to attract students, academicians, and researchers from around the world. The conference focuses on key areas, including Civil Engineering, Computer Engineering/Science, Electronics Engineering, Mechanical Engineering, and Environmental Science. This volume includes carefully reviewed research papers written by passionate contributors who share our dedication to excellence. Each paper undergoes rigorous evaluation by national and international experts to ensure its quality and relevance. I express my sincere thanks to our reviewers for their critical insights and efforts in maintaining high academic standards. Their expertise plays a crucial role in elevating these proceedings to an international level. In addition, we hosted two symposiums during the conference. The first was the Symposium on Traffic and Transportation Engineering, organized in collaboration with the Society of Transport Engineers Nepal (SOTEN) and Safe & Sustainable Travel Nepal (SSTN). The second was the Symposium on Environment, Energy, and Water, held in collaboration with the Center for Research for Environment, Energy, and Water (CREEW). Finally, I would like to sincerely thank Kantipur Engineering College for trusting us with the responsibility of organizing this prestigious event. Their continuous support and commitment to academic excellence have been vital to our success. Best Regards, _______________ Er. Pralhad Chapagain Editor-in-Chief 7th Conference on Engineering and Technology KEC Conference 2025